Lampah: expression canvas of Java’s spirituality in the new media art - Ario Wibisono; Bambang Sunarto; Santosa Soewarlan (ASSOCIATION FOR SCIENTIFIC COMPUTING ELECTRICAL AND ENGINEERING (ASCEE), 2022)
Malioboro is an integral part of the architectural artwork of the city of Yogyakarta, which is full of meaning, philosophy, and noble values of Javanese culture. Currently, Malioboro has developed into a tourist area and a quite existing public cultural space. However, along with the times, the philosophical meaning and noble values embedded in the architecture of the city of Yogyakarta by HB I as the founder of Ngayogyakarta Hadiningrat seem to be unclear and increasingly difficult to read. The video art installation Lampah is a form of creative response to the existence of contemporary Malioboro as a public space as well as a meaningful piece of architectural art. By using interpretative-subjective approaches and artistic methods, the creator reads this phenomenon and represents it in the form of Lampah artwork. As a contemplative space, 'Lampah' also offers an alternative way to transform Javanese noble values and spirituality by using idioms and ways of speaking in Javanese culture. Models in architecture are used to complete the design of this work. It is hoped that this concept can provide new insights and discourses in art, especially new media art